Students’ Perception on Wall Magazine Project toward their English Writing Performances and Creativity Skill : A Project-based Learning Implementation at Paragraph Writing Class - Nofenti Mardalena Halawa; Dian Safitri (Universitas Negeri Padang, 2023)
This study aimed to reveal students’ perception on wall magazine project toward their writing performance and their creativity skill. The population of this study was English literature students of English Department in UNP. It consists of five classes who are in the academic year 2022/2023. The sample of this study was all classes of literature students. The sample was taken using simple random sampling technique. Total number of the sample in this research was 31 students. The researcher used descriptive research design. The data were collected through a questionnaire. According to the research, in writing performance, the result of this research shows that students had a positive perception on content (3.18), organization (3.18), and very positive perception on mechanics (3.30), and vocabulary (3.28). Meanwhile, in creativity skill, students' perceptions of their creativity skill during paragraph writing class were positive in generating ideas (3.18) and listening to the inner voice (2.99), and very positive in digging deeper into ideas (3.30) and openness and courage in exploring idea (3.27). Students also enjoy to learn paragraph writing class by using the wall magazine project..